Intrapersonal Communication of Male Students Regarding Mental Health Treatment in Malaysia: A Study on Perception Theory - Nadya Annisa; Putri Surya Cempaka (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2020)
The purpose of this study is to gain clarity on the perception process of male students group in Malaysia in seeking mental health care. This study conducted interviews with participants, then the results of the interviews were analysed to determine the process of intrapersonal communication related to mental health care issues. The results found that there are three themes which are the perceptual processes in intrapersonal communication. The conclusions of this study are theoretical implications for academics in the field of intrapersonal communication and practical implications for society regarding the issue of mental health care.